Identification and Characterization of Two Transmembrane Proteins Required for Virulence of Ustilago maydis - Weiland, Paul; Altegoer, Florian (Frontiers in Plant Science, 2021)
Smut fungi comprise a large group of biotrophic phytopathogens infecting important crops such as wheat and corn. Through the secretion of effector proteins, the fungus actively suppresses plant immune reactions and modulates its host's metabolism. Consequently, how soluble effector proteins contribute to virulence is already characterized in a range of phytopathogens. However, membrane-associated virulence factors have been much less studied to date. Here, we investigated six transmembrane (TM) proteins that show elevated gene expression during biotrophic development of the maize pathogen Ustilago maydis. We show that two of the six proteins, named Vmp1 and Vmp2 (virulence-associated membrane protein), are essential for the full virulence of U. maydis. The deletion of the corresponding genes lead to a substantial attenuation in the virulence of U. maydis. Furthermore, both are conserved in various related smuts and contain no domains of known function. Our biochemical analysis clearly shows that Vmp1 and Vmp2 are membrane-associated proteins, potentially localizing to the U. maydis plasma membrane. Mass photometry and light scattering suggest that Vmp1 mainly occurs as a monomer, while Vmp2 is dimeric. Notably, the large and partially unstructured C-terminal domain of Vmp2 is crucial for virulence while not contributing to dimerization. Taken together, we here provide an initial characterization of two membrane proteins as virulence factors of U. maydis.